Psychological stress responses to COVID-19 and adaptive strategies in China. (December 2020) - Song, Mingke
Highlights: Measures of quarantine and social-distancing to contain COVID-19 spread caused an extent of stress responses in the general public. The front-line medical workers, COVID-19 patients and their relatives were more susceptible to psychological disorders. China issued principles and guidelines for psychological crisis intervention to help affected people get out mental stress. The strategies to COVID-19 stress and encountered difficulties during implementation may provide implications for other countries. Abstract: The novel coronavirus disease 2019 (COVID-19) developed into a pandemic on March 11. COVID-19 not only brought life crisis, but also incurred psychological stress: tension, anxiety, fear and despair among affected populations. How to help people overcome traumatic stress reactions and get out of psychological crisis has become a public concern that needs to be resolved in time. This article reported the psychological responses caused by the COVID-19 epidemic in China based on relevant experience and studies. The anti-epidemic measures of self-quarantine and social-distancing were deployed to contain the spread of COVID-19, but inevitably caused a certain extent of side effect: frustration and anxiety in the general public. Especially, the front-line medical rescue staff and COVID-19 patients were more susceptible to developing psychological disorders. Correspondingly, adaptive strategies and public health policies were rapidly implemented in China to deal with outbreak-caused mental stress. The psychological impact of COVID-19 and coping strategies adopted in China provided warning and reference for countries that are and going to be affected by this natural disaster.